Soap operas and fertility: Evidence from Brazil - Eliana La Ferrara; Alberto Chong; Suzanne Duryea (Inter-American Development Bank, Research Department, 2008)
This paper focuses on fertility choices in Brazil, a country where soap operas (novelas) portray families that are much smaller than in reality, to study the effects of television on individual behavior. Using Census data for the period 1970-1991, the paper finds that women living in areas covered by the Globo signal have significantly lower fertility. The effect is strongest for women of lower socioeconomic status and for women in the central and late phases of their fertility cycle. Finally, the paper provides evidence that novelas, rather than television in general, affected individual choices.
Keywords: 330; Fernsehprogramm; Manipulation; Verhalten; Frauen; Familienplanung; Brasilien